INTERTEXTUAL STUDY “WHEN YOU WERE MINE BY REBECCA SERLE AND ROMEO & JULIET BY WILLIAM SHAKESPEARE” - Annisa Annisa; Harianto II Harianto II (Fakultas Sastra UMN AL Washliyah, 2021)
This paper entitled Intertextual Study “When Were Mine by Rebecca Serle and Romeo & Juliet by William Shakespeare”. The research method is a qualitative descriptive method with an intertextual approach. The problem discussed in this article is how the intertextual relationship between